Solute Transport Model for Open Channel Flow - Nor Azlina, Alias; Lariyah, Mohd Sidek (College of Engineering, Universiti Tenaga Nasional, 2018)
A numerical model is expected to become the primary tool in predicting the flow depth of any flood event. Apart from simulating the flood flow, a solute transport model is found to be an important aspect as it could spread by the flood flows. Due to development in computer technology, a two-dimensional (2D) model has become popular in flow modeling and its associated processes such as in solute transport. However, in certain cases of modelling the flood event, the modeller would probably face difficulty in resolving the problematic river flow in a 2D manner. Hence, a one-dimensional (1D) model with the ability to deal with complex hydrodynamic flows is needed. This paper presents a 1D solute transport numerical model development. The St. Venant equations for an open channel flow and the advection-diffusion equation are used to simulate both shallow and contaminated flows simultaneously. The model has been validated and the results obtained show a good agreement when compared to the analytical solutions.